The effect of gross domestic product and equalization funds on poverty in districts in the Province of Aceh - Eliza Fatmi; Sirojuzilam Sirojuzilam; Irsad Irsad (Jurnal Mantik, 2023)
This study aims to analyze the effect of GRDP and Balance Fund (General Allocation Fund, Special Allocation Fund, and Aceh Special Autonomy Fund on) Poverty in Districts / Cities in Aceh Province. This study uses secondary data from 2010 to 2020 in 23 districts/cities in Aceh Province. The analysis model used is the panel data analysis model using the Eviews 10 analysis tool. Based on the results of the model selection test using the Chow and Hausmant tests shows that the Fixed Effect Model (FEM) is the best model for this research model. Based on the Fixed Effect Model (FEM) research results, Gross Regional Domestic Product General Allocation Fund and have a negative and significant effect on poverty. While the Special Allocation Fund has a negative but insignificant effect and Aceh's Special Autonomy is still very much needed, based on the results of the particular autonomy fund research, it has a positive and little impact on poverty in the District / City of Aceh Province. The correlation result (Adj-R2) of this research variable is 0.93911.